Z dziejów relikwii świątobliwej Ofki Piastówny, dominikanki raciborskiej - Stefaniak, Piotr (Śląskie Studia Historyczno-Teologiczne, 2011)
Daughter of Przemysł of Racibórz and duchess of Upper Silesia, Euphemia was one of the holy women of the Piast dynasty. At the age of fourteen, she entered the convent founded by her father, the Racibórz Dominicans, where, with time, she became a prioress. Shortly after her death on January 17, 1359, she became famous for miracles. A strong though local cult soon started to grow around her relics, causing her to be called blessed as early as the 16th century. Today, the Diocese of Opole, in conjunction with the unwavering cult of Eufemia, is seeking the beatification of this holy Piast duchess to officially sanction her holiness. It is frequently the case with many holy royalty, such as Hedwig of Silesia, Cunegund or Yolande, that many posthumous remains undergo an evolution. They start with the typical royal funeral, yet end up buried in shrines dedicated to the veneration of saints. So it was with Euphemia. Initially, as a former prioress, she was buried in a chapel crypt in the church of the Racibórz Dominicans. According to the original plans, the chapel was designed as a mausoleum of the Racibórz line of Piasts; hence Euphemia belonged there by birth. At the end of the 16th century, the existing cult transformed the burial chapel into a shrine, particularly after 1738 when the tomb of Euphemia was adopted to the public cult. The relics of the Piast duchess remained in the crypt until 1821. During the secularization of the convent, they were moved to the church of the Assumption of our Lady. In 1930, thanks to the pastor, Georg Schulz, a neo-baroque burial altar was built for Euphemia. Finally, in the spring of 1945, Euphemia’s altar shared the fate of the entire city and was burned by the soldiers of the Red Army. On one hand, the history of Euphemia’s relics testifies to the intensity of the religious cult she received over centuries; on the other, it places her in the burial tradition of the Piast holy women. The story of Euphemia becomes unique in 1821 when her relics were removed from the shrine destroyed by its new protestant owners and were moved to the church of the Assumption. Today the memory of Euphemia continues to grow. Przeł. Małgorzata Lekan OP